Strategi komunikasi image restoration mantan narapidana kasus narkoba di Aceh Tengah - ALI MUSTAFA; Syukur Kholil; Hasan Sazali (Jurnal Studi Komunikasi, 2023)
In general, former prisoners want to participate socially so that their status is the same as that of other members of society. However, in reality, they often face social discrimination and negative stigma from their environment. This research question is: What is the message from former convicts in drug cases in the strategy to restore self-image in Central Aceh Regency? This research uses qualitative methods to obtain in-depth and natural data. Image Restoration Theory by William L. Benoit's is used as an analytical perspective. The research informants were four former drug convicts who had been socially reintegrated according to certain criteria. Data collection was carried out using unstructured interviews. Research data was analysed using the interactive model by Miles, Huberman, and Saldana. This study found that the informants use a transcendental-multi-step flow communication model in their image restoration strategies. The messages used by informants in image restoration include the five strategies offered by Benoit. However, corrective action and mortification are important strategies in this case. The corrective action strategy is not just about being "clean" from drugs but also about making positive changes in various aspects, such as relationships, work, and religious practice. Apart from having a cognitive consonance effect, the mortification strategy can also repair damaged relationships. Through corrective action and mortification strategies, former prisoners build an image called the "image of repentance".